PENERAPAN METODE RELIABILITY CENTERED MAINTENANCE ( RCM ) PADA MESIN CAKE BREAKER CONVEYOR DI PABRIK KELAPA SAWIT ( PKS ) - Hakim, Legisnal; Sunaryo, Sunaryo; Puji, Ari Andriyas; Denur, Denur (Jurnal Teknik Industri Terintegrasi (JUTIN), 2021)
Oil palm plantations and their processing units are expected to grow rapidly, advances in science and technology are very fast along with sophisticated equipment created to simplify and speed up a production process in a palm oil factory, one of which is the Cake Breaker Conveyor (CBC) which functions to break/separate oil palm kernels. core of the shell in oil palm kernel processing. Problems that often occur in the process of separating pulp with palm kernel are in the transfer Cake Breaker Conveyor (CBC). This study tries to propose a machine maintenance system using the application of the RCM (Realibility Centered Maintenance) method on the CBC Cake Breaker Conveyor machine, where the RCM (Realibility Centered Maintenance) method is an identification technique with the intention of saving costs and maintenance to minimize the risk and impact of failure. in facilities and equipment utilities. From the test results the Mean Time to Failure (MTTF) value of the CBC engine clutch (Cake Breaker Conveyor) is 1,803 Hours. While the calculation results of the Mean Time to Repair (MTTR) value of the CBC engine clutch (Cake Breaker Conveyor) is 4:00 Hours Types of Preventive Maintenance and Time Based Maintenance For the optimal maintenance interval for the CBC (Cake Breaker Conveyor) engine clutch is 19 days. Keywords : Cake Breaker Conveyor, Realibility Centered Maintenance, Palm Oil Mill